A National Perspective of Do-Not-Resuscitate Order Utilization Predictors in Intracerebral Hemorrhage. (January 2016) - Patel, Achint A.; Mahajan, Abhimanyu; Benjo, Alexandre; Jani, Vishal B.; Annapureddy, Narender; Agarwal, Shiv Kumar; Simoes, Priya K.; Pakanati, Krishna Chaitanya; Sinha, Vikash; Konstantinidis, Ioannis; Pathak, Ambarish; Nadkarni, Girish N.
Nontraumatic intracerebral hemorrhage (ICH) is associated with substantial morbidity and mortality. Do-not-resuscitate (DNR) orders are linked to poorer outcomes in patients with ICH, possibly due to less active management. Demographic, regional, and social factors, not related to ICH severity, have not been adequately looked at as significant predictors of DNR utilization. We reviewed the Healthcare Cost and Utilization Project's Nationwide Inpatient Sample (NIS) database in 2011 for adult ICH admissions and DNR status. We generated hierarchical 2-level multivariate regression models to estimate adjusted odds ratios. We analyzed 25 768 ICH hospitalizations, 18% of which (4620 hospitalizations) had DNR orders, corresponding to national estimates of 126 254 and 22 668, respectively. In multivariable regression, female gender, white or Hispanic/Latino ethnicity, no insurance coverage, and teaching hospitals were significantly associated with increased DNR utilization after adjusting for confounders. There was also significantly more interhospital variability in the lowest quartile of hospital volume. In conclusion, demographic factors and insurance status are significantly associated with increased DNR utilization, with more individual hospital variability in low-volume hospitals. The reasons for this are likely qualitative and linked to patient, provider, and hospital practices.